Photosynthetic Response to Elevated Temperature in the Symbiotic Dinoflagellate Symbiodinium microadriaticum in Culture - Iglesias-Prieto, Roberto; Matta, Jaime L.; Robins, Wendy A.; Trench, Robert K. (Proceedings of the National Academy of Sciences - PNAS, 1992)
Elevated temperature (28-34⚬C) has been hypothesized as the primary cause of the loss of algal endosymbionts in coral reef-associated invertebrates, a phenomenon observed on a world-wide scale over the last decade. In past studies of this "bleaching" phenomenon, there has been an underlying assumption that temperature adversely affects the animal hosts, the algae thereby being relegated to a more passive role. Because photosynthesis is a sensitive indicator of thermal stress in plants and has a central role in the nutrition of symbiotic invertebrates, we have tested the hypothesis that elevated temperature adversely affects photosynthesis in the symbiotic dinoflagellate Symbiodinium microadriaticum. The results, based on analyses of light-mediated O2evolution and in vivo fluorescence, indicate that photosynthesis is impaired at temperatures above 30⚬C and ceases completely at 34-36⚬C. These observations are discussed in the context of possible mechanisms that may function in the disassociation of algal-invertebrate symbioses in response to elevated temperature.